Pemijahan Dan Penanganan Larva Ikan Betok (Anabas Testudineus Bloch) Pada Media Air Gambut - Hendri Bugar; Kartika Bungas; Shinta Sylvia Monalisa; Ivone Christiana (Fakultas Peternakan Universitas Kristen Palangka Raya, 2013)
The purpose of this study was to determine the effectiveness of the stimulation of carp pituitary extract on the spawning of climbing perch and also to determine the effectiveness of the use of natural food results from fertilization to climbing perch larval survival. After the granting of pituitary extract increased the diameter of the eggs at the end of treatment A (0.70 mm) = 125 eggs, treatment B (0.70 mm) = 125 eggs, treatment C (0.70 mm) = 135 eggss. While climbing perch without pituitary extract (treatment D) egg at the end diameter there is still a size 0.50 mm = 4 eggs, 0.60 mm = 87 eggs and 0.70 mm = 109 eggs. After mixing climbing perch brood, the treatment A, B and C courtship and spawning occurs as a result of gonadotropin stimulation by the pituitary gland extract. Relative growth rate of climbing perch larvae given natural food reared for 1 month ranged 11208.00% - 6982.61%. Relative growth rate fastest in treatment C fed with 60 liters of filtered with an average relative growth rate 11208.00%. Treatment A and B decreased the relative growth rate, because natural food given limited and may not be used for growth.